Perlecan (HSPG2) promotes structural, contractile, and metabolic development of human cardiomyocytes - Benjamin B. Johnson; Marie-Victoire Cosson; Lorenza I. Tsansizi; Terri L. Holmes; Tegan Gilmore; Katherine Hampton; Ok-Ryul Song; Nguyen T.N. Vo; Aishah Nasir; Alzbeta Chabronova; Chris Denning; Mandy J. Peffers; et al. (Cell Reports, 2024)
Summary: Perlecan (HSPG2), a heparan sulfate proteoglycan similar to agrin, is key for extracellular matrix (ECM) maturation and stabilization. Although crucial for cardiac development, its role remains elusive. We show that perlecan expression increases as cardiomyocytes mature in vivo and during human pluripotent stem cell differentiation to cardiomyocytes (hPSC-CMs). Perlecan-haploinsuffient hPSCs (HSPG2+/−) differentiate efficiently, but late-stage CMs have structural, contractile, metabolic, and ECM gene dysregulation. In keeping with this, late-stage HSPG2+/− hPSC-CMs have immature features, including reduced ⍺-actinin expression and increased glycolytic metabolism and proliferation. Moreover, perlecan-haploinsuffient engineered heart tissues have reduced tissue thickness and force generation. Conversely, hPSC-CMs grown on a perlecan-peptide substrate are enlarged and display increased nucleation, typical of hypertrophic growth. Together, perlecan appears to play the opposite role of agrin, promoting cellular maturation rather than hyperplasia and proliferation. Perlecan signaling is likely mediated via its binding to the dystroglycan complex. Targeting perlecan-dependent signaling may help reverse the phenotypic switch common to heart failure.